Students` Opinions about the Use of Geogebra Computer Program as a Technological Tool in Mathematics Lessons - Recep Bilgin; Hamdi Serin (International Journal of Social Sciences & Educational Studies, 2022)
Students’ attitudes towards mathematics are generally negative. The difficulty of the course has an important role in the development of this attitude. However, with some new arrangements to be made, students can be interested in the lesson. In this study, it is discussed to what extent the GeoGebra program makes the mathematics content attractive. For this purpose, two separate Likert scale questionnaires were applied to 12th grade students. In the first of the questionnaires, students’ attitudes towards mathematics were determined. In the second, students’ attitudes towards the GeoGebra program were revealed. Accordingly, students have increased their interest in mathematics a little bit thanks to the GeoGebra program.